Digital Migration Infrastructure in return-writing: visualizing the migration landscape of India - Mukherjee, Preetha; Menon, Nirmala (Frontiers in Sociology, 2024)
Digitization has carved out the migration patterns of immigrants over the recent years of increased technological interventions in human mobility. Migration infrastructures, which typically refer to the physical, commercial, humanitarian, and governmental modes of operation, are multidimensional in nature. Digital infrastructures are equally important to the physical ones as digital technologies facilitate these migration processes through agents like hardware, software, and mediating actors. Amongst the multiple forms of migration, the concept of return-writing and nostalgia-struck-returnees encompass individuals whose life trajectories run parallel to the homeland. The narrative of return to the homeland emerges aβs a dominant motif in literature due to the rising trends of globalization, the writers’ reflection on their own migrant experiences, and publishing trends meeting the demand of the global book market. The objective is to assess the role of digital migration infrastructures in return migrations to India through a close reading of the selected texts and review of postcolonial literary theories by using conditional operation in Python. The study here explores the varied nuances of return migration with a primary focus on the external conditions of travel in migration literature. The paper aims to analyze the genre of return-writing in Indian English literature, through three novels over a period of two decades, i.e., from 2000–2023. The selected texts, beginning with Amit Chaudhuri’s A New World (2000), Gun Island (2019) by Amitav Ghosh, and Devika Rege’s novel Quarterlife (2023), offer a panoramic view of return migration. These novels are extensive in the time period of technological interventions and in depiction of return migration. The Python code examines the extent of existence of a set of digital migration infrastructure keywords by analyzing the content of the novels and creates bar plots and charts to offer a visual representation of the classification results. The resulting trend traces the increased intervention of Digital Migration Infrastructure in the recent migration literature.